On the 70th anniversary of the beginning of the scientific activity of entomologist and arachnologist Nikolay Borisovich Shlykov - Abukenova, V.S. (Fundamental and Experimental Biology, 2023)
Karaganda Buketov University has been distinguished by highly professional scientific and pedagogical personnel since its formation. This was determined by the continuity of the creative potential of the Karaganda Pedagogical Institute. Nikolay Borisovich Shlykov the associate professor of the Faculty of Natural Sciences was among the generalists of the Pedagogical Institute. He was a brilliant professional biologist. He received practical training in the Entomology Laboratory of the Institute of Zoology of the Republic of Kazakhstan and became a first-class scientist and teacher. He developed entomological and arachnological research at the university. Shlykov was the first head of the Zoology Department of the Faculty of Natural Sciences of the Karaganda Pedagogical Institute from 1960 to 1965. At that time, he was engaged in the formation of new areas of scientific work, selected personnel and directed the development of fundamental zoological training courses. His scientific publications on the biology of poplar pests, fauna and ecology of spiders are relevant and valuable sources of information for modern scientists. The high level of quotability of N.B. Shlykov’s data is the result of unique accuracy and content. This is a sample of research work for many generations of his students.